Pengembangan Lembar Kerja Berbasis Discovery Learning untuk Meningkatkan Kemampuan Pemecahan Masalah - Sari, Nindy Novita; Haryani, Sri (Chemistry in Education, 2020)
Problem solving is one of the abilities that students must master. In fact, the mastery of this ability is still low and the teaching material used in learning lacks training of students' problem solving abilities. Therefore, this study aims to analyze the feasibility discovery learning-based worksheet to improve students' problem solving abilities. The type of research used is Research and Development with a 4D model modified to 3D (define, design, development). The study was conducted at SMA N 1 Rembang with the subjects of class XII MIPA 5, XI MIPA 7 and XI MIPA 8. Data collection using expert validation sheets, readability questionnaires and response questionnaires. The results of expert validation gave very good responses with an average score of material experts at 3,38 and media experts at 3,6. The results of the analysis of the questionnaire responses of students gave good responses with an average score of 49,95. Overall, the research results show that the discovery learning-based worksheet to improve student's problem solving abilities is feasible to be used in chemistry learning of salt hydrolysis material.